Injury patterns associated with personal mobility devices and electric bicycles: an analysis from an acute general hospital in Singapore - King, Christelle Cha Sow (Singapore Med J, 2020)
INTRODUCTION: The increasing popularity of personal mobility devices (PMDs) and electric bicycles (e-bikes) in Singapore has met with growing public concern over safety. Following the passing of the Active Mobility Bill, there remains a gap in the local literature in terms of injury patterns arising from the use of these devices. METHODS: A retrospective study was conducted on the Singapore National Trauma Registry (SNTR) from the emergency department of an acute hospital from 1 January 2016 to 31 December 2016. All patients with injuries related to the use of PMDs and e-bikes were included. Data captured included demographic information, device used and injury severity score (ISS). RESULTS: The 259 patients identified had a mean age of 32.1 years and a male predominance. Most (83.4%) were injured from falling off their devices. Devices commonly associated with injury were scooters, skateboards and motorised bicycles. Most injuries were mild (94.6%, ISS < 9) and were mainly external wounds (89.2%) and upper and lower limb injuries (35.5%). There was no difference in ISS in terms of the device used (motorised vs. non-motorised). More severe injuries (ISS ≥ 9) were caused by e-bikes (42.9%) and electric scooters (28.6%). Factors associated with these injuries were older age, use of e-bikes, and injuries to the head, face and thorax. Most patients (86.1%) were discharged and one died. CONCLUSION: While most injuries associated with PMDs and e-bikes are minor, serious injuries could result from their use. The SNTR should be updated to include PMDs and e-bikes as a category.